2013
DOI: 10.1210/jc.2012-3390
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Anandamide and RelatedN-Acylethanolamine Levels Occur in the Peripheral Blood of Women With Ectopic Pregnancy and Are Mirrored by Changes in Peripheral Fatty Acid Amide Hydrolase Activity

Abstract: Elevated endocannabinoid levels and reduced FAAH activity are associated with ectopic pregnancy and may modulate tubal function, suggesting dysfunctional endocannabinoid action in ectopic implantation. Oleoylethanolamide may play a critical role in embryo-tubal transport.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 39 publications
3
21
0
Order By: Relevance
“…FAAH activity is not limited to AEA; however, and has been shown to metabolize all of the NAEs [28]. Much less is known about the role of 2-AG in the regulation of pregnancy; however, it as also been shown to be regulated in the uterus as a function of the ovarian cycle [29] Therefore, the interplay between progesterone and the eCS is complex and not fully understood [14; 15; 2325]. …”
Section: Introductionmentioning
confidence: 99%
“…FAAH activity is not limited to AEA; however, and has been shown to metabolize all of the NAEs [28]. Much less is known about the role of 2-AG in the regulation of pregnancy; however, it as also been shown to be regulated in the uterus as a function of the ovarian cycle [29] Therefore, the interplay between progesterone and the eCS is complex and not fully understood [14; 15; 2325]. …”
Section: Introductionmentioning
confidence: 99%
“…25 High maternal peripheral blood endocannabinoid levels modulated by low FAAH activity in lymphocytes can inhibit successful pregnancy after in vitro fertilization, 26,27 and were recently associated with ectopic pregnancy possibly through tubal dysfunction. 28 Endocannabinoids have also been implicated in blood pressure regulation. 29 Endocannabinoids can cause vasodilation through CB1, TRPV1 and nitric oxide (NO)-mediated or NO-independent mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Cui et al [95, 96] found reduced FAAH expression in the endometrium of patients with PCOS and an increase in AEA plasma levels, as FAAH is mainly involved in AEA degradation. Previous studies have shown that elevated plasma AEA levels in connection with a lower FAAH activity resulted in ectopic pregnancy which is also linked to PCOS [85, 97]. Thus, it seems likely that a dysregulation of the ECS is involved in pregnancy complications of women with PCOS.…”
Section: The Ecs In Gynecological Disorders and Cancermentioning
confidence: 99%